Performing Musicalization Of Poetry And Uploading The Video On Youtube For Poetry Class Project - Lestari, Febriyanti Dwiratna (English Education Department, Universitas Islam Indonesia, 2012)
Musicalization of poetry is an intriguing class project for English Literature students. It enables them to dig into their creativity and talent in writing and performing poetry and at the same time speeding up their comprehension of English poetry, particularly from the aspect of musical device of a poem. Though not treated as the main activity of the course, such task is valuable, acommodating those interested more in producing literary work than merely criticizing it. Also, to make this project more fun, the students can be challenged to videotape their performance and share it on YouTube. The students are thus encouraged to pack it in a good video presentation because their videos, once uploaded and set public, become available for any viewers. This project may work best if assigned for a group work because the students could delegate jobs such as who is to write and recite the poem, to design the concept of their musicalization of poetry, to tape and edit the video, and finally to upload the video on YouTube and promote it on social media like Facebook and Twitter. Indeed, musicalization of poetry project could be taken as an extra assignment in poetry class by which the students practice employing the poetic devices at first hand. This paper will explain the why, what and how this class project should be conducted.Key words: musicalization of poetry, YouTube video upload, poetry class project